Hmong herbal medicine and herbalists in Lao PDR: pharmacopeia and knowledge transmission - Jean Marc Dubost; Chiobouaphong Phakeovilay; Chithdavone Her; Audrey Bochaton; Elizabeth Elliott; Eric Deharo; Mouachan Xayvue; Somsanith Bouamanivong; Geneviève Bourdy (BMC, 2019)
Abstract Background In Lao PDR, the Hmong ethnic group has extensive knowledge about the use of medicinal plants. However, despite the importance of the Hmong pharmacopeia as a primary health care resource, no study has been undertaken to thoroughly document medicinal plant knowledge and its transmission. Objectives of this study are (i) to describe and characterize Hmong pharmacopeia, and (ii) to understand how medicinal plant knowledge is transmitted and spread among Hmong in Lao PDR, in order to assess whether this knowledge base is under threat. Methods In order to describe Hmong pharmacopeia, a total of 14 interlocutors were interviewed in three provinces (Bokeo, Xieng Khouang, and Vientiane), using "walk in the wood" methodology. To gain insight about knowledge transmission, semi-structured interviews were conducted with 28 people. Twenty of them were herbalists. Data analysis was performed using univariate analysis for the description of the pharmacopeia. Medicinal plant knowledge consistency was assessed through use and plant name overlapping. Answers to the semi-structured interview on knowledge transmission were analyzed qualitatively. Results Three hundred thirty-three different medicinal species were collected. The majority of uses attributed to plants were gastrointestinal conditions (22% of total use reports), gynecological conditions and sexually transmitted disease (12%), skin affections (8%), kidney and bladder problems (5%), physical traumas (5%), and aphrodisiac (or male tonics; 5%). Use convergences are more marked in the gynecological sphere, but there is a strong heterogeneity in practices and knowledge. Medicinal plant knowledge transmission is oral, gained from direct experience since childhood, matrilineal, and kept strictly within the family lineage. Apparent limited consensus on uses might stem from the method of knowledge transmission and to the economic value given to medicinal plants. Discussion Use pattern of species from the Hmong pharmacopeia does not appear to be strikingly different from the national Lao pharmacopeia. Differences may lie in the methods and reasons for knowledge transmission. It can be proposed that the economic value given to plants helps in keeping the knowledge alive, and encourages its transmission. Conclusion Hmong traditional medicine is constantly evolving in a dynamic process and aims to respond to health problems faced by the local population. Herbalists appear as health fully fledged actors and should be recognized and valued as such.